Alterations in Skin Immune Response Throughout Chronic UVB Irradiation—Skin Cancer Development and Prevention by Naproxen - Gonzalez Maglio, Daniel Horacio (2010)
Skin exposure to UVB radiation has been reported to produce both a significant inflammatory response and marked immunosuppression. This work was aimed to evaluate whether the response of murine skin to an acute UVB dose was modified by pre-exposure to chronic UVB irradiation and by topical treatment with naproxen, a nonsteroidal anti-inflammatory drug. Moreover, the effect of naproxen on the incidence of UV-induced skin tumors was studied. Prostaglandin E2 (PGE2) and tumor necrosis factor alpha (TNF-a) levels were increased 96 h post-UVB in acutely irradiated animals and both mediators were modi.ed by topical naproxen application?PGE2 was decreased while TNF-a was increased. Such inflammatory response was suppressed when mice were chronically irradiated. Naproxen application on chronically irradiated mice reduced the incidence of tumor lesions. Taken together, our data suggest that chronic UVB irradiation generates an immunosuppressive state that prevents skin cells from responding normally to an acute irradiation challenge, thus impairing the protective effect of TNF-a against skin tumor development. Furthermore, reduction in the incidence of tumor lesions by naproxen may be due to its ability to increase TNF-a levels as well as to decrease PGE2.